Mechanical Examination of Swords in the Eastern Mediterranean from the Late Bronze Age to the Early Iron Age - Kopanias, K.; Vemou, E.; Sidiropoulou, K. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
This paper offers a new approach for studying the functionality of swords, by conducting mechanical tests on 3D models of swords created in Solidworks, a computer-aided design (CAD) and computer-aided engineering (CAE) program. The main aim of this study is to investigate the functional role and thus the capacity of a variety of swords of Late Bronze Age (LBA) and Early Iron Age (EIA) from the Aegean to the Near East. During the latter part of the LBA and EIA, swords gradually played an ever-increasingly important role in the Eastern Mediterranean and the Near East (Drews 1993: 33-163; Molloy 2010: 421; Schulz 2014: 259; Mehofer and Jung 2017: 397). In recent years, numerous studies have been dedicated to them, examining their typology, their symbolic role and their use as weapons. The restricted accessibility and the limited publications for use wear analysis or experimentation on Near Eastern swords (in contrast with the Aegean material), along with the high-cost of experimental studies, turned our attention towards 3D modelling. Solidworks offers the possibility to design a variety of swords and create a controlled virtual environment in order to evaluate their resistance to force and therefore examine their capability as weapons. This method allows us to determine whether the swords had the necessary structural integrity which would allow them to withstand a significant amount of force applied to them and creates opportunities for future fruitful collaboration with metal wear analysis and experimental archaeology, in order to understand better the manner of use of these weapons. Our method offers an answer to the following question: was it possible to use the LBA-EIA swords in actual fighting and how much force could they handle?